Perlindungan Hukum Terhadap Pencipta Lagu Akibat Pengunggahan Kembali Ke Media Youtube: Analisis Putusan Nomor 913 K/Pdt.Sus-HKI/2022 - Shafiyah Laila Andini; Jur Rizal Sofyan Gueci (JOURNAL of LEGAL RESEARCH, 2025)
The main issue addressed in this study is the increasing number of copyright infringements in the field of songs and music, particularly by irresponsible parties who re-upload television broadcasts to YouTube, as examined in Court Decision No. 913 K/Pdt.Sus-HKI/2022. The purpose of this study is to identify the judicial considerations in Decision No. 913 K/Pdt.Sus-HKI/2022 regarding the legal protection of songwriters and to analyze the determination of compensation for the creators. This research employs a normative legal method using both the statute approach and the case approach. The findings indicate that, in accordance with Law No. 28 of 2014 on Copyright, copyright disputes are resolved through civil lawsuits filed with the Commercial Court, and no appeal mechanism is available. The judicial considerations in Decision No. 913 K/Pdt.Sus-HKI/2022 are deemed appropriate, as they refer to the relevant provisions of Law No. 28 of 2014 and other applicable regulations and government decrees. This decision reaffirms the state’s role in protecting creators’ moral and economic rights in the digital era.